Oleuropein Attenuates Lipopolysaccharide-Induced Acute Kidney Injury In Vitro and In Vivo by Regulating Toll-Like Receptor 4 Dimerization - Cui, Yushun; Gao, Hongwei; Han, Shan; Yuan, Renyikun; He, Jia; Zhuo, Youqiong; Feng, Yu-Lin; Tang, Meiwen; Feng, Jianfang; Yang, Shilin (Frontiers in Pharmacology, 2021)
Acute kidney injury(AKI) is a common critical illness that involves multiple systems and multiple organs with a rapid decline in kidney function over short period. It has a high mortality rate and presents a great treatment challenge for physicians. Oleuropein, the main active constituent of Ilex pubescens Hook. et Arn. var. kwangsiensis Hand.-Mazz., displays significant anti-inflammatory activity, although oleuropein’s therapeutic effect and mechanism of action in AKI remain to be elucidated. The present study aimed to further clarify the mechanism by which oleuropein exerts effects on inflammation in vitro and in vivo. In vitro, the inflammatory effect and mechanism were investigated through ELISA, Western blotting, the thermal shift assay, co-immunoprecipitation, and immunofluorescence staining. Lipopolysaccharide (LPS) induced acute kidney injury was employed in an animal model to investigate oleuropein’s therapeutic effect on AKI and mechanism in vivo. The underlying mechanisms were investigated by Western blot analysis of kidney tissue. In LPS-stimulated macrophages, our data demonstrated that oleuropein significantly reduced the expression of inflammatory mediators like NO, IL-6, TNF-α, iNOS, and COX-2. Moreover, oleuropein inhibited NF-κB/p65 translocation, and had a negative regulatory effect on key proteins in the NF-κB and MAPK pathways. In addition, the thermal shift and co-immunoprecipitation assays revealed that oleuropein played an essential role in binding to the active sites of TLR4, as well as inhibiting TLR4 dimerization and suppressing the binding of TLR4 to MyD88. Oleuropein markedly alleviated LPS induced acute kidney injury, decreased serum creatinine and blood urea nitrogen (BUN) levels and proinflammatory cytokines. More importantly, the TLR4-MyD88-NF-κB/MAPK pathways were confirmed to play an important role in the oleuropein treatment of AKI. In this study, oleuropein exhibited excellent anti-inflammatory effects by regulating TLR4-MyD88-NF-κB/MAPK axis in vitro and in vivo, suggesting oleuropein as a candidate molecule for treating AKI.